2018
DOI: 10.3390/antibiotics7020050
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergism of Silver Nanoparticles with Antibiotics as an Alternative Treatment in Multiresistant Uropathogens

Abstract: The increase in the prevalence of bacterial resistance to antibiotics has become one of the main health problems worldwide, thus threatening the era of antibiotics most frequently used in the treatment of infections. The need to develop new therapeutic strategies against multidrug resistant microorganisms, such as the combination of selected antimicrobials, can be considered as a suitable alternative. The in vitro activities of two groups of conventional antimicrobial agents alone and in combination with silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…The recorded MICs values of AgNPs in the current study come very close to the values reported previously [18] when AgNPs of an average size of 8.23 nm ± 0.91 nm were tested against MDR uropathogens including E.coli, Klebsiella, P.aeruginosa and Acinetobacter isolates with MIC values of (8, 4, 8 and 16 µg/ml). Higher MIC values of 31.25µg/ml and 62.5µg/ml were reported [19] on using 11-21 nm AgNPs against E.coli and Klebsiella pneumoniae, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The recorded MICs values of AgNPs in the current study come very close to the values reported previously [18] when AgNPs of an average size of 8.23 nm ± 0.91 nm were tested against MDR uropathogens including E.coli, Klebsiella, P.aeruginosa and Acinetobacter isolates with MIC values of (8, 4, 8 and 16 µg/ml). Higher MIC values of 31.25µg/ml and 62.5µg/ml were reported [19] on using 11-21 nm AgNPs against E.coli and Klebsiella pneumoniae, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study [18] strongly supports the obtained results recording a synergistic effect of AgNPs of 8.23 nm size and at concentration of 4-16 µg/ml where a decrease in the MIC of amikacin by 16, 2, 8, 32 folds against E.coli, Klebsiella, P.aeruginosa and Acinetobacter isolates were recorded. These findings locate within our recorded ranges against the same isolates respectively (2-16, 2-16, 2-32 and 8-32).…”
Section: Discussionsupporting
confidence: 88%
“…The results indicate synergism when the corresponding FICI ≤ 0·5, addition when 0·5 < FICI ≤ 1, indifference when 1 < FICI ≤ 4 and antagonism when the FICI > 4 (Lopez‐Carrizales et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Among the most studied nanomaterials are silver nanoparticles due to their antimicrobial activity against Gram-positive and Gram-negative bacteria. They can be used in combinatorial treatments with currently used antibiotics for enhanced antimicrobial activity (Shahverdi et al, 2007;Kora and Rastogi, 2013;Naqvi et al, 2013;Singh et al, 2013;Panácek et al, 2016;Lopez-Carrizales et al, 2018;Perveen et al, 2018;Vazquez-Muñoz et al, 2019). Nonetheless, some other MNPs FIGURE 2 | Antimicrobial treatment strategies: (A) disadvantages of using single drugs and (B) advantages of using combinatorial treatments.…”
Section: Metal Nanoparticle-based Combinatorial Treatmentsmentioning
confidence: 99%